please tell me the above questions answer.
Attachments:
![](https://hi-static.z-dn.net/files/db4/098bcb8e520d940d9dae63d935c233f7.jpg)
Answers
Answered by
0
Hey mate here is your answer!!
Show that = A(B X C) = B( C X A ) = C( A X B)
AB + AC = BC + AB = AC + BC
= AB - AB = AC - AC = BC- BC
= 0
Hope my answer is correct
Please mark as brainlaist!!
Show that = A(B X C) = B( C X A ) = C( A X B)
AB + AC = BC + AB = AC + BC
= AB - AB = AC - AC = BC- BC
= 0
Hope my answer is correct
Please mark as brainlaist!!
sagarvineet4gmailcom:
Hii
Similar questions